How is professionals' information seeking shaped by workplace procedures? A study of healthcare clinicians. Issue 3 (May 2019) - Hertzum, Morten; Simonsen, Jesper
Highlights: Procedures shape information seeking differently for uncertain and equivocal tasks. Triage procedure specifies which information to retrieve and how to interpret it. During triage coordinating nurses rarely seek information, they pattern match. Timeout procedure makes space for collaborative reflection and information seeking. Junior and expert professionals benefit dissimilarly from timeout procedure. Abstract: Professional work is often regulated by procedures that shape the information seeking involved in performing a task. Yet, research on professionals' information seeking tends to bypass procedures and depict information seeking as an informal activity. In this study we analyze two healthcare tasks governed by procedures: triage and timeouts. While information seeking is central to both procedures, we find that the coordinating nurses rarely engage in information seeking when they triage patients. Inversely, the physicians value convening for timeouts to seek information. To explain these findings we distinguish between junior and expert professionals and between uncertain and equivocal tasks. The triage procedure specifies which information to retrieve but expert professionals such as the coordinating nurses tend to perform triage, which is an uncertain task, by holistic pattern recognition rather than information seeking. For timeouts, which target an equivocal task, the procedure facilitates information seeking by creating a space for open-ended collaborative reflection. Both junior and expert physicians temporarily suspend patient treatment in favor of this opportunity to reflect on their actions, though partly for different reasons. We discuss implications for models of professionals' information seeking.